UJI DAYA HAMBAT PERASAN BAWANG PUTIH TERHADAP PERTUMBUHAN SALMONELLA TYPHI - Vinenthy, Luh Putu Intan Visva; Habibah, Nur; Dhyanaputri, I Gusti Ayu Sri (Politeknik Kesehatan Tanjung Karang, 2019)
Garlic is one of the herbs that widely used by people to cure the disease, which caused by a bacterial infection. Garlic contains Allicin which has an antibacterial effect on Salmonella typhi. Several studies have been proved that garlic has antibacterial activity against the growth of microbes. This research was conducted to study the potential effect of the garlic juice inhibitory on the growth of Salmonella typhi bacteria. This research was used experimental post-test only control design and disc diffusion method with MHA media. This study was carried out by using four different concentration there were 20, 40, 60 and 80%. The negative and positive control was used sterile aqua dest and chloramphenicol. The inhibition zone was determined by observing the clear zone around the disk. The result of the data analysis using the Least Significant Difference (LSD) showed that there was a significant difference between each concentration of the garlic juice. The obtained results proved that garlic juice affects the inhibition zone of Salmonella typhi growth. The largest inhibitory zone was found at the concentration of 80% with the diameter inhibition zone was 23 mm. This diameter inhibitory zone was classified as a very strong inhibitory effect category. These results concluded that there was a linear correlation between inhibitory potential with the concentration of garlic juice.